Integrative Physiological, Transcriptional, and Metabolic Analyses Provide Insights Into Response Mechanisms of Prunus persica to Autotoxicity Stress - Shen, Wanqi; Zeng, Chunfa; Zhang, He; Zhu, Kaijie; He, Hao; Zhu, Wei; He, Hanzi; Li, Guohuai; Liu, Junwei (Frontiers in Plant Science, 2021)
Autotoxicity is known as a critical factor in replanting problem that reduces land utilization and creates economic losses. Benzoic acid (BA) is identified as a major autotoxin in peach replant problem, and causes stunted seedling growth or even death. However, the physiological and molecular mechanisms of peach response to BA stress remain elusive. Here, we comprehensively studied the morphophysiological, transcriptional, and metabolic responses of peach plants to BA toxicity. Results showed that BA stress inhibited peach seedlings growth, decreased chlorophyll contents and fluorescence levels, as well as disturbed mineral metabolism. The contents of hydrogen peroxide, superoxide anion, and malondialdehyde, as well as the total antioxidant capacity, were significantly increased under BA stress. A total of 6,319 differentially expressed genes (DEGs) were identified after BA stress, of which the DEGs related to photosynthesis, redox, and ion metabolism were greatly changed; meanwhile, numerous stress-responsive genes (HSPs, GSTs, GR, and ABC transporters) and transcription factors (MYB, AP2/ERF, NAC, bHLH, and WRKY) were noticeably altered under BA stress. BA induced metabolic reprogramming, and 74 differentially accumulated metabolites, including amino acids and derivatives, fatty acids, organic acids, sugars, and sugar alcohols, were identified in BA-stressed roots. Furthermore, an integrated analysis of genes and metabolites indicated that most of the co-mapped KEGG pathways were enriched in amino acid and carbohydrate metabolism, which implied a disturbed carbon and nitrogen metabolism after BA stress. The findings would be insightful in elucidating the mechanisms of plant response to autotoxicity stress, and help guide crops in alleviating replant problem.